Electron collisions in atmospheres. Issue 2 (2nd April 2016) - Campbell, L.; Brunger, M.J.
Abstract : Collisions with electrons from several sources are common throughout planetary atmospheres. While in most circumstances direct electron impact is less significant than solar radiation, electron collisions have a major influence on the chemistry driven by both photon and particle impact. This review addresses electron collisions in atmospheres, with emphasis on cases where electron impact drives, enhances, or otherwise interacts with chemical processes. Understanding of atmospheric processes typically involves computational simulation based on theory, remotely-sensed atmospheric data, atomic and molecular physics data and chemical reaction rates. These and the modelling techniques will therefore also be covered. An example of current and future work on electron impact on the hydroxyl radical ( OH) is presented, where applications in both atmospheric studies and plasma medicine are important.